The Justly Killed Imam: a Muʿtazilī Defense of the Murder of ʿUthmān b. ʿAffān (r. 23–36/644–656) - Anthony, Sean W. (Journal of Abbasid Studies, 2025)
This article revisits the attribution of the Kitāb al-Maqālāt, a previously unknown heresiological text, to the renowned Muʿtazilī theologian Abū ʿAlī al-Jubbāʾī. Discovered in a Yemeni manuscript compilation and first studied by Hassan Ansari in 2016, the work’s authenticity and authorship have been subjects of scholarly debate, particularly after the publication of the first scholarly edition in 2019. By examining its polemical treatment of the ʿUthmāniyya and its defense of the regicide of ʿUthmān b. ʿAffān, this study analyzes the doctrinal and rhetorical strategies employed in the Maqālāt and compares them to both early Muʿtazilī discourse and mature Sunni orthodoxy. Through textual analysis and historical contextualization, the article argues that the work’s treatment of the ʿUthmāniyya and the murder of ʿUthmān casts significant doubt on its attribution to Abū ʿAlī al-Jubbāʾī.